Management of Dual Health Asset Applications Developed by The Ministry of Internal Affairs and Ministry of Health in Hospitals in Boyolali, Central Java, Indonesia - Yunita Rusdiyanti; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2020)
Background: The management of health assets in Hospitals is a complex matter. State-onwed Hospitals use two applications from the Ministry of Internal Affairs developed by the Development Audit Agencynamely Regional Management Information System of Regional Assets (Simda BMD) and the Ministry of Health namely Application of Infrastructure and Medical Devices (ASPAK). This study aims to determine the management of health assets based on the applications of the Ministry of Internal Affairs and the Ministry of Health in three Regional Public Hospitals in Boyolali Regency.Subjects and Method: This was a descriptive-qualitative study using a study case approach. This study was carried out in three Regional Public Hospitals in Boyolali Regency. The main informants were goods treasurer, warehouse section, staff in charge of planning and reporting section, staff in charge of ASPAK,  head of medical support, and head of administrative subdivision. The data were collected using in-depth interviews, non-participative observation, and document observation. The data were analyzed using three  main steps namely data reduction, data display, and conclusion drawing.Results: The staff in charge of asset management in RSUD Boyolali had a sufficient proficiency in the asset concept and management by using the two applications. However, not all steps were conducted on time andfollowing the guidance.Conclusion: The training is required to improve the capability of the staff in charge of asset management. A system is also required  to link the  two applications to provide more efficient input system and create inter operability.Keywords: asset managementCorrespondence: Yunita Rusdiyanti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: y_rusdiyanti@yahoo.com. Mobile: 081-22981365.Journal of Health Policy and Management (2020), 05(03): 189-196https://doi.org/10.26911/thejhpm.2020.05.03.04.